การวิเคราะห์วิธีการเขียนบทละครสำหรับสื่อมวลชน : บทเรียนจากงานของสมสุข กัลย์จาฤก - ขจีรัตน์ หินสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objectives of this research were to accumulate technique of playwriting for mass media specifically referred to radio and television plays written by Somsuk Kanjaruek who was a professional playwright. The analysis of her biography, internal and external factors that would effect the playwriting for mass media and gathering proper qualifications of playwright for mass media from opinion of Somsuk Kanjaruek. The result of the research has shown that internal factors which effect her ability of playwriting initiates from her own characteristics, education, family members, as well as the marriage to the person working in radio entertainment business gave her the opportunity to write playwriting for radio, whereas, external factors which drive her career as to be a playwright is to minimize the production cost. The writing has been adapted to the development of media and audience demands. Thus, her being in the mass media production business by herself is one of many factors that give her freedom in playwriting to a certain degree. The knowledge derived from the analysis technique of playwriting for mass media of Somsuk Kanjaruek is that it initiates from searching idea from many resources such as experience of self and others, mass media, history, original plot and imagination, before expanding it into a plot. The factors that a playwright should consider are content, worthiness, profit, investor, audience, budget & performance, competitors, timing & scheduling, and social rules & regulations. The next step is expanding the plot into a play, these 6 elements-title, theme, plot, characters, dialogue, and setting. In radio playwriting, these 3 factors-listener group, timing & scheduling and vocal media should be considered while in writing television script, the playwright should considered these 5 factors-whether the story is from original or adapted novel, objectives, nature of televised media, viewers and timing & scheduling. In Somsuk Kanjaruek s opinion, good qualifications of playwright for mass media include those characteristic of a general artist, the comprehension of narrative techniques in the from of plays, its production process, as well as, the acceptance of the fact that entertainment as plays for mass media and commerce are inseparable. Thus, good playwright for mass media should be able to compromise and balance the arts and commerce to create a perfect playwriting.